2022
DOI: 10.3389/fcvm.2022.1005030
|View full text |Cite
|
Sign up to set email alerts
|

Vein morphometry in end-stage kidney disease: Teasing out the contribution of age, comorbidities, and vintage to chronic wall remodeling

Abstract: BackgroundChronic kidney disease (CKD) is a highly comorbid condition with significant effects on vascular health and remodeling. Upper extremity veins are important in end-stage kidney disease (ESKD) due to their potential use to create vascular accesses. However, unlike arteries, the contribution of CKD-associated factors to the chronic remodeling of veins has been barely studied.MethodsWe measured morphometric parameters in 315 upper extremity veins, 131 (85% basilic) from stage 5 CKD/ESKD patients and 184 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…One donor had history of hypertension (38F) and none had diabetes. We did not observe significant differences in morphometry between upper arm basilic and cephalic veins ( S1 Fig ), in agreement with published data [ 15 ].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…One donor had history of hypertension (38F) and none had diabetes. We did not observe significant differences in morphometry between upper arm basilic and cephalic veins ( S1 Fig ), in agreement with published data [ 15 ].…”
Section: Resultssupporting
confidence: 93%
“…Therefore, unlike arterial diseases, the cells contributing to venous IH may not need to dedifferentiate extensively or migrate from the adventitia. Phenotypic similarities between intimal and medial SMCs, their pro-remodeling transcriptional profiles, and the widespread distribution of fibroblasts may also explain the tendency of veins to chronically develop IH and fibrosis [ 15 ]. Ultimately, comparative studies with veins obtained after vascular surgeries will be necessary to evaluate the true cellular contributors to postoperative IH and their molecular differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our team previously reported the following: (1) endogenous metabolites, including lysophospholipids [10], can bind to their intrinsic receptors, rather than classical damage-associated molecular pattern (DAMP) receptors, such as toll-like receptors (TLRs) and nod-like receptors/inflammasomes, and become conditional DAMPs; (2) CKD uremic toxins (UTs) serve as conditional DAMPs/homeostasis-associated molecular patterns (HAMPs) to modulate inflammation [11]; (3) upregulated secretomes in peripheral blood mononuclear cells (PBMCs) from patients with CKD and ESRD act synergistically with UTs to promote inflammation and potential disease progression [12]; (4) under pathological conditions, the aorta may act as an immune organ via the upregulation of a variety of secretomes and promote trained immunity [13]; and (5) endothelial cells in the CKD environment can serve as innate immune cells with innate immune memory function by reprograming metabolic pathways [14]. We also reported that CKD contributes to morphometric vascular changes in upper-extremity veins [15]. However, a few important questions remain poorly characterized, including whether CKD pathology contributes to the chronic remodeling and reprogramming of upper-extremity veins into immune endocrine organs and whether CKD primes (trains) upper-extremity veins to fail during the arteriovenous fistula (AVF) creation process.…”
Section: Introductionmentioning
confidence: 80%